Maize: Nutrition Dynamics and Novel Uses 2013
DOI: 10.1007/978-81-322-1623-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Maize Utilisation in Food Bioprocessing: An Overview

Abstract: Fermented foods are considered as palatable and wholesome foods prepared from raw or heated raw materials and appreciated for their attributes such as pleasant flavour, aroma, texture, improved processing properties and better digestibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…In ancient times, it was one of the most important cultural components used by peninsular Mayans in offerings to the gods and spirits in ceremonies related to maize cultivation and harvest (Vassallo Rodríguez, 2016). It is currently consumed in southeastern Mexico, where it remains as a food of nutritional, cultural, and economic importance (Sangwan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In ancient times, it was one of the most important cultural components used by peninsular Mayans in offerings to the gods and spirits in ceremonies related to maize cultivation and harvest (Vassallo Rodríguez, 2016). It is currently consumed in southeastern Mexico, where it remains as a food of nutritional, cultural, and economic importance (Sangwan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Males tend to fall closer to the C 4 ‐protein line than females, suggesting that the most notable difference between male and female diets in Moquegua was the amount of C 4 ‐protein consumption. As discussed above, fermenting maize can enhance the protein content and make certain amino acids more bioavailable (Hamad and Fields, ; Umoh and Fields, ; Wacher‐Rodarte, ; Sangwan et al, ). While high δ 13 C collagen values could also result from greater consumption of C 4 plant fed animals, such as guinea pigs ( Cavia porcellus ) or llamas ( Llama glama ), bone δ 15 N collagen values are not significantly different between the sexes, suggesting that diets did not differ in terms of meat consumption.…”
Section: Discussion: Diet and Gender In Tiwanakumentioning
confidence: 99%
“…Importantly, laboratory studies have demonstrated that the fermentation of many cereal grains raises their protein quality by making certain amino acids more available. In particular, the fermentation of maize can increase the total amount of protein and the bioavailability of lysine, an essential amino acid (Hamad and Fields, ; Umoh and Fields, ; Wacher‐Rodarte, ; Sangwan et al, ). Compared with other grains, maize exhibits a relatively low protein content (Cordain, ), and thus consumption of fermented maize products, such as chicha , might be expected to exhibit higher δ 13 C collagen values than an individual who consumed an equal amount of unfermented maize.…”
Section: Methodsmentioning
confidence: 99%
“…During the production of Tejuino, the temperature, types of microorganisms, pH, production zone, and fermentation time are variables that determine the nutritional and microbiological composition [6]. The fermentation process for Tejuino is spontaneous and uncontrolled, principally for the artisanal kind; therefore, the sensory characteristics and quality are important variables due to several microorganism types being involved, such as the Saccharomyces genus and LAB, principally [7]. These microorganisms contribute to the flavor development through a carbohydrate metabolism, proteolysis, and amino acid catabolism, as well lipolysis and a fatty acids metabolism [4,5,8].…”
Section: Introductionmentioning
confidence: 99%